Identidade de marca, gestão e comunicação - Vásquez, Ruth Peralta (Organicom, 2007)
This article addresses the study of brands from the aspect of their identities. Thus, not unlike personal identity, a brand identity also carries a series of elements by which it is characterized and that ascribe to it a personality. The article shows the role played by brand identity, its communication and its resulting transformation into image.